Clinical Syndromes of Cerebral Venous Thrombosis: An Institutional Study - Ajit Prasad Mishra; Shubhankar Mishra; Ashok Kumar Mallick (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Cerebral Venous Sinus Thrombosis (CVST) is a neurovascular syndrome in contrast to more common arterial disease. Despite advances in the recognition of CVST in recent years, diagnosis and management can be difficult because of the diversity of underlying risk factors and the absence of a uniform treatment approach. Aim: To evaluate the syndromes associated with the CVST spectrum and its association with veins with detailed prognostication. Materials and Methods: The present hospital-based, observational study was conducted in the Department of Neurology, Sri Ramachandra Bhanja Medical College and Hospital, Cuttack, Odisha, India. A total of 52 patients of age >14 years, who presented with radiological confirmation of venous sinus thrombosis were included in the study. All their clinical and epidemiological parameters were tabulated. They were classified into four clinical syndromes namely syndrome of raised intracranial hypertension without focal deficit, syndrome of the focal neurological deficit with or without raised intracranial hypertension, syndrome of cavernous thrombosis and syndrome of early altered consciousness with involuntary movements/ diffuse encephalopathy. Clinical parameters were analysed according to syndromic presentation. Statistical analysis was done using Statistical Package for the Social Sciences (SPSS) software version 24.0. Results: A total of 52 patients with radiological confirmation of CVST were evaluated over a period of two years. The mean age of presentation was 31.8±12.3 years. The mean duration of symptoms prior to hospitalisation was 13.6±11.9 days. Sensorium was normal in most of the admitted patients. In the present study, syndrome-2 (syndrome of focal neurological deficit) was the most common syndromic reported (n=32, 61.6%). Conclusion: Cerebral venous sinus thrombosis should be classified according to the syndromic association of clinical features. It will help in easy diagnosis based only on assessment of the clinical features.